2018
DOI: 10.1101/451971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel genome-wide associations for suicidality in UK Biobank, genetic correlation with psychiatric disorders and polygenic association with completed suicide

Abstract: Background: Suicide is a major issue for global public health. 'Suicidality' describes a broad clinical spectrum of thoughts and behaviours, some of which are common in the general population.Methods: UK Biobank recruited ~0·5 million middle age individuals from the UK, of whom 157,000 completed an assessment of suicidality. Mutually exclusive groups were assessed in an ordinal genome-wide association study of suicidality: 'no suicidality' controls (N=83,557); 'thoughts that life was not worth living' (N=21,06… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 26 publications
(21 reference statements)
2
42
1
1
Order By: Relevance
“…In line with previous studies 4 , 7 , 8 , our PRS analysis confirmed the genetic overlap of MD with outcomes related to suicidality spectrum. However, we did not find any interactive effect between MD PRS and polysubstance dependence in the context of SI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies 4 , 7 , 8 , our PRS analysis confirmed the genetic overlap of MD with outcomes related to suicidality spectrum. However, we did not find any interactive effect between MD PRS and polysubstance dependence in the context of SI.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, we conducted a discovery GEWIS to verify whether SDs interact with the individual genetic variability in the context of SI. Finally, based on the high genetic overlap between suicidality and depression observed across multiple large-scale GWAS 4 , 7 , 8 , we verified whether depression genetic risk interacts with polysubstance dependence in the context of suicidality spectrum. Supplemental Fig.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…10,11,[13][14][15][16][17][18] In humans, an autosomal-dominant DCC mutation results in structural and functional alterations in the connectivity of mesocortical pathways, with an associated decrease in novelty-seeking behaviour and cigarette use. 19,20 An increasing number of meta-analyses of genome-wide association studies and postmortem human studies have shown that altered levels of DCC expression and the presence of specific genetic polymorphisms in the DCC gene are associated with psychiatric conditions, 21 most notably major depressive disorder, 15,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] schizophrenia 34,[36][37][38] and drug abuse. 19,[39][40][41][42] A study by the Cross-Disorder Group of the Psychiatric Genomics Consortium 3 revealed that a PFC-enriched network of genes prominently affected 8 psychiatric disorders, and a DCC single nucleotide polymorphism (SNP) showed the highest pleiotropic association with all 8 disorders.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS summary statistics for each environment were accessed via the UKB (see http://www.nealelab.is/uk-biobank) and formatted with Linkage Disequilibrium Score Regression (LDSC) using the 1000 Genomes Project European populations as a linkage disequilibrium reference panel. 18 GWAS summary statistics for suicidality were retrieved from Strawbridge, et al 7 All environments and the ordinal suicidality phenotype exhibited significant heritability (h 2 ) with h 2 z-scores ≥ 4, indicating sufficient power for genetic correlation. After multiple testing correction (FDR<5%), suicidality was genetically correlated with all but four environments: UKB Field ID 738: average total household income before tax, UKB Field ID20525: able to pay rent/mortgage as an adult, UKB Field ID 20527: been involved in combat or exposed to war-zone, and UKB Field ID 20491: someone to take you to doctor when needed as a child ( Figure S3).…”
Section: Introductionmentioning
confidence: 99%